Improving Students' Learning Skills and Outcomes by Using Learning Media of English Movie at The 11th Science Class 3 Of MAN 3 Banjarmasin In 2018/2019 - Purwanti Purwanti (Jurnal PTK dan Pendidikan, 2019)
This conducted research is about the learning media application of English movie to overcome the students’ low listening skill and learning outcomes of the 11th science class at MAN 3 Banjarmasin on English subject. This study is also aimed to find out how the teacher activities, student activities and student responses to the use of English movie learning media. It used a class action research (CAR) design with 2 cycles. Each cycle consists of planning, implementing actions, observing and evaluating as well as analyzing and reflecting. The subjects in this study were 36 students of the 11th Science Class. Data collected using observation techniques, written tests and questionnaires. Then the data was analyzed with the techniques of quantitative descriptive and qualitative analysis. The results showed that the use of English movie learning media in the learning activities can improve the teacher activities, student activities, students' listening skill, and learning outcomes which the students give a good impact on the application of English movie learning media.